2007
DOI: 10.1080/03009740701393957
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary involvement in patients with early rheumatoid arthritis

Abstract: Lung abnormalities are frequently observed in patients with early RA on HRCT, even when CXR and PFTs are normal. Limited areas of GGOs were the abnormalities depicted exclusively in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
6

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 40 publications
2
54
0
6
Order By: Relevance
“…All the other abnormalities were found in the control group at the same frequency as in the patients. DAS-28, PFT, and the Larsen score showed no significant correlations with either each HRCT sign score separately or the total score 7 .…”
Section: To the Editormentioning
confidence: 69%
See 1 more Smart Citation
“…All the other abnormalities were found in the control group at the same frequency as in the patients. DAS-28, PFT, and the Larsen score showed no significant correlations with either each HRCT sign score separately or the total score 7 .…”
Section: To the Editormentioning
confidence: 69%
“…The third point is that no control group was included in their study (healthy nonsmokers). Our group investigated the pulmonary abnormalities in patients with early RA using high resolution computed tomography (HRCT) 7 . For this reason 43 patients with early RA were included.…”
Section: To the Editormentioning
confidence: 99%
“…Sensitive diagnostic methods such as high resolution computed tomography (HRCT) have revealed structural changes in the lungs in early disease. Metafrazi found lung abnormalities, including ground glass opacities, among 69% of 43 never-smoking patients with early RA, but not in control subjects [133]. Demourelle has reported structural lung changes among ACPA positive non-smoking subjects [134], indicating that other irritants than cigarette smoke may contribute to the initial inflammatory process preceding clinically manifest RA.…”
Section: The Lungsmentioning
confidence: 99%
“…This demonstrated that the synovium in ACPA-positive patients is initially normal, even in patients who later develop clinical arthritis. In addition, existing evidence suggests that a proportion of patients with positive RA serology may already have HRCT parenchymal lung changes at time of RA diagnosis (Gabbay et al, 1997, Metafratzi et al, 2007, Reynsdottir et al, 2011. In fact, a retrospective study by Gizinski et al (2009) showed that positive RA serology can be found in smokers with ILD without symptoms and signs of RA, but who may later develop RA.…”
Section: Environmental Triggers Of Pulmonary Inflammationmentioning
confidence: 99%